Structural order and charge transfer in highly strained carbon nanobelts - YAVUZ, İLHAN (ROYAL SOC CHEMISTRY, 2020)
We present a computational study of the atomic morphology, structural order, and charge transfer properties of radially pi-conjugated, closed-loop, and highly strained chiral carbon nanobelts (CNBs). The synthesis of nanobelts has recently been achieved [G. Povie, Y. Segawa, T. Nishihara, Y. Miyauchi and K. Itami,Science, 2017,356, 172-175] and they are considered to be precursors for carbon nanotube synthesis, or in some cases are considered to be a field of application by themselves. Tightly packed solid-state arrays of CNBs are nest-like, similar to carbon nanorings. Molecular dynamics simulations reveal that the solid-state order is largely stable. We estimated the charge transport properties with electronic structural methods. DFT-calculated reorganization energy is found to be 201 meV. Due to the radial pi-conjugation and weak intermolecular contacts, the charge transfer electronic coupling between molecular pairs in the solid-state was relatively weak and around 10 meV. The charge transport mobility was simulated by the kinetic Monte Carlo methods and the hole mobility was estimated to be 0.4 cm(2)V(-1)s(-1)for the disordered CNBs. It was also found that the hole mobility had sizable anisotropy even in the disordered state. Given the exceptional optoelectronic properties of exotic molecules such as C(60)and carbon nanotubes, chiral CNBs and their possible derivatives, as the building blocks of these molecules, will revolutionize such applications.
Keywords: ELECTRON-TRANSFER; ATOMIC CHARGES; TRANSPORT; CYCLOPARAPHENYLENES; MOLECULES; AMBER